iAct – Apps on Google Play - Roger Federer Foundation
The Roger Federer Foundation initiated and supported the development of this interactive learning and teaching methods course that was specially designed for the Zambian Community School context. In particular, a school-based, collaborative approach is promoted and the Zambian primary school curriculum is referenced in various exemplary lesson plans and activities. The course does however have a wider application and may be flexibly implemented with minor contextual adaptations and while a collaborative learning approach is strongly encouraged, the course materials are also suitable for individual study purposes. The course will provide teachers with the skills to: ● Plan, prepare and implement activities for interactive learning ● Adapt content and design age and grade appropriate activities ● Collect, make and store learning and teaching resources made from materials found in the local environment ● Manage interactive learning in large and multi-grade classes ● Manage interactive learning in mixed ability classes: Teaching or mediating content and knowledge for ALL learners regardless of ability ● Promote an enabling learning environment by creating safe classrooms in which all learners are heard and in which all learners are supported to succeed. Specific course focus areas and topics include: ● Planning and preparing activities for whole class, pair and group work in different contexts and /or for learners of different abilities ● Learning to make language and literacy, maths and science resources for teaching and learning from natural and commercial waste materials found in the local environment.